Pengaruh program latihan untuk mengembangkan daya tahan otot dan kekuatan tubuh bagian atas pada pemain karate tingkat lanjut - Hala Fahim Aliwi; Janan Naji Kamel; Abbas Zaki Abdul Hussein (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The importance of motor abilities lies in enabling player to perform frequent and rapid combat movements efficiently and effectively without a decrease in performance or exposure to rapid stress, which is necessary especially during fights that require constant effort and high rhythm. Proceeding from this importance, the research aimed to prepare a training program to develop muscular endurance and arm strength among advanced karate players, and to identify impact of this program in developing those abilities. Materials and methods. The researchers used the experimental approach to design the two equivalent groups (experimental and control), and the sample number was (18) advanced karate players who were deliberately selected, and then randomly divided into two groups of (9) players for each group. The pilot group underwent the training program developed, while the control group continued its traditional training. The implementation of the training program lasted for two months, from 7/1/2025 to 6/3/2025. Before and after tests were conducted on, the two groups to measure the level of endurance of muscular strength and characteristic strength with speed, and the results were analyzed using appropriate statistical methods. Results. The results showed a clear superiority of the experimental group over the control group, which indicates the effectiveness of the training program in developing the targeted capabilities. Adopting this program within the training plans prepared for advanced karate players because of its clear positive impact on improving physical performance. indicated that the development of strength endurance is achieved when working at 60-70% of the maximum strength with high repetitions and short rest, which is the method used in the current program. Conclusion. The training program showed clear effectiveness in improving muscular endurance and upper body speed characteristic strength in advanced karate players, compared to the control group. This improvement was attributed to the integration of resistance and biometric exercises with combat movements, resulting in effective neuromuscular adaptation and improved skill performance.